SMEs Success: Roles of Financial Literacy, Capital Structure, and Innovation - Retno Cahyaningati; Alifi Tria Susanti; Kartika Ayu Kinanti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
This study examines the roles of financial literacy and capital structure in improving SME performance, with innovation as a mediating variable. Using a quantitative causal design, data were collected from 425 SME owners and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that financial literacy has a significant positive effect on innovation, but no direct effect on SME performance. In contrast, capital structure significantly affects both innovation and SME performance. Innovation also has a significant positive effect on performance and serves as a key mechanism in the model: it fully mediates the relationship between financial literacy and SME performance. It partially mediates the relationship between capital structure and SME performance. These findings contribute to the SME literature by showing that financial capability and financing decisions do not automatically improve performance unless they are translated into innovation. Practically, the study suggests that SME development programs should combine financial literacy training with innovation support. At the same time, financing policies should enable balanced capital structures that help SMEs invest in product, process, and service innovation. This study is limited by its cross-sectional design and self-reported data, which may restrict causal generalization over time.